COMPREHENSIVE ASSESSMENT OF THE LIVER AFTER LAPAROTOMY IN DONOR MULTIORGAN - M.S. Hubutia; V.A. Gulyaev; L.N. Zimina; M.S. Novrusbekov; M.G. Minina (Вестник трансплантологии и искусственных органов)
The macroscopical evaluation of the liver of 310 donors is presented and the ball estimation of liver quality is develo- ped. In 181 cases the retrospective morphological evaluation was performed (58.6%) undesirable pathology of donor liver – the fatty dystrophy (steatosis) was frequent. It is proved that most trustworthy information about the condition of donor liver is its complex evaluation including visual survey and biopsy with staining on fat that. It coned promote increase in a donor pool at 10%.